2009
DOI: 10.1016/j.vaccine.2009.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Functional and biological determinants affecting the duration of action and efficacy of anti-(+)-methamphetamine monoclonal antibodies in rats

Abstract: IntroductionMonoclonal antibody (mAb) medications offer promising treatment for autoimmune disease, cancer, and a host of other diseases including substance abuse [1][2][3]. These medications have several advantages over traditional small molecule medicines. For example, mAbs have high affinity and precise selectivity for their disease targets, act as pharmacokinetic antagonists to block or blunt the action of their target antigen, and have an extremely long biological halflife (e.g., ~21 days for human IgG 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 22 publications
2
58
1
Order By: Relevance
“…[1][2][3][4][5] Anti-METH mAbs reside in the blood and extracellular fluid compartments where they bind METH with such high affinity that they rapidly redistribute METH from its sites of action in the brain and other organs into the blood stream. [6][7][8] MAbs offer specific advantages as a drug abuse therapy. Compared with other immunotherapies such as vaccines, mAbs necessarily do not require the function of the user's immune system to work, making them appropriate for immunosuppressed patients, including those with HIV/AIDS or autoimmune conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Anti-METH mAbs reside in the blood and extracellular fluid compartments where they bind METH with such high affinity that they rapidly redistribute METH from its sites of action in the brain and other organs into the blood stream. [6][7][8] MAbs offer specific advantages as a drug abuse therapy. Compared with other immunotherapies such as vaccines, mAbs necessarily do not require the function of the user's immune system to work, making them appropriate for immunosuppressed patients, including those with HIV/AIDS or autoimmune conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An additional important characteristic is the duration of in vivo activity. We have shown that despite having a similar biological half-life to other mAbs (i.e., »6-7 d in the rat 6 ), one of our highest affinity anti-METH mAbs only effectively reduces METH effects for a short time period. 2 The reasons for this in vivo inactivation have not been completely determined, 9 but the ability to reduce the effects of repeated METH doses over an extended time period is important for long-term success of new mAbs.…”
Section: Introductionmentioning
confidence: 89%
“…2 Anti-METH mAbs function via pharmacokinetic antagonism of METH effects. By dramatically altering the disposition of METH via high-affinity binding and redistribution, 1,6 they reduce its stimulant effects. 1,2 The binding interactions between METH and mAb are, however, complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously suggested that the blood-brain barrier restricts anti-METH mAb (but not METH) to the vasculature, which allows temporary greater drug-mAb occupancy and more removal of METH from the brain with each passage through the brain vasculature (Laurenzana et al, 2009).…”
Section: Introductionmentioning
confidence: 99%